Functional and Quality Analysis of Nutrition-Related Mobile Apps Available in Poland Using the MARS Scale - Taszarek, Beata; Książek, Ewelina; Konikowska, Klaudia (Analiza funkcjonalna i jakościowa aplikacji mobilnych związanych z żywieniem dostępnych w Polsce z wykorzystaniem skali MARS (Mobile Application Rating Scale), 2025)
Aim: The aim of this study was to evaluate the functionality and quality of nutrition-related mobile apps available on the Polish market through the App Store (Apple Inc.) using a standardised assessment tool, the Mobile App Rating Scale (MARS). Methodology: The selection of apps was based on clearly defined inclusion and exclusion criteria, following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. App quality was assessed using the MARS tool, known for its high reliability (α = 0.90; r = 0.79). Evaluations were conducted by two independent teams, each consisting of two reviewers who evaluated every app over a two-week period. The final scores were established through consensus. Results: The study revealed significant variability in the quality of the evaluated apps. MyFitnessPal received the highest overall quality rating, while Monitor Postu Przerywanego was given the lowest rating. In terms of subjective quality, YAZIO, FatSecret, and MyFitnessPal achieved the highest scores, whereas Monitor Postu Przerywanego once again received the lowest rating. The most significant potential for user impact was found in YAZIO and MyFitnessPal, with Monitor Postu Przerywanego demonstrating the lowest potential in this sector. Implications and recommendations: The findings underline the need for improvement in nutrition-related apps by integrating reliable, evidence-based content, personalised dietary recommendations, and advanced technological solutions. Collaboration with nutrition experts and the implementation of certification systems are also recommended to enhance user trust. Whilst these apps show potential in supporting healthy habits, further optimisation in terms of quality and functionality is essential. Originality: This article offers a comprehensive evaluation of the quality and functionality of nutrition apps available on the Polish market, utilising the standardised MARS tool. Its originality lies in combining a systematic approach with hands-on user evaluation, taking into account the technical criteria and also the potential to influence health-related behaviour.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2025, Nr 41, s. 42-54
Keywords: mobile apps; dietary apps; nutrition; Mobile App Rating Scale; mHealth; aplikacje mobilne; aplikacje dietetyczne; żywienie; Skala Oceny Aplikacji Mobilnych; zdrowie mobilne